A SEMANTIC STUDY OF LINGUOCULTURAL ELEMENTS IN ENGLISH AND UZBEK FAIRY TALES AND THEIR TRANSLATION CHALLENGES (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article presents a semantic analysis of linguocultural elements in English and Uzbek fairy tales, focusing on how culturally embedded meanings are constructed, represented, and transferred across languages. Drawing on examples from both oral and written folklore traditions, the study identifies key linguocultural units such as culturally marked metaphors, symbolic motifs, kinship terms, forms of address, and idiomatic expressions. The research employs semantic and contextual analysis to uncover how these units function within their respective cultural narratives and how they shape readers’ conceptual understanding. Special attention is given to translation challenges arising from culture-specific meanings, untranslatable concepts, pragmatically loaded expressions, and differing narrative conventions. The study argues that literal translation often fails to convey the deep cultural significance encoded in these elements, and that successful translation requires interpretive strategies such as cultural substitution, explicitation, descriptive translation, or functional equivalence. The findings highlight the necessity of culturally informed translation approaches to preserve both the semantic depth and the aesthetic impact of linguocultural elements in fairy tales. The article contributes to comparative folklore studies and translation theory by demonstrating the semantic mechanisms through which culture influences meaning and by outlining practical solutions for translators working between English and Uzbek.